Administration of metformin alleviates atherosclerosis by promoting H2S production via regulating CSE expression. Issue 3 (23rd July 2019) - Ma, Xiaofeng; Jiang, Zhisheng; Wang, Zuo; Zhang, Zhuhua
Abstract: The therapeutic effect of metformin (Met) on atherosclerosis was studied here. Effects of methionine and Met on the induction of inflammatory response and H2 S expression in peritoneal macrophages were evaluated. Enzyme‐linked immunosorbent assay, immunohistochemistry assay, western blot, and quantitative reverse transcription polymerase chain reaction were conducted to observe the levels of cystathionine γ‐lyase (CSE), DNA methyltransferases 1 (DNMT1), DNMT3a, DNMT3b, tumor necrosis factor (TNF‐ α), interleukin 1b (IL‐1β), and hydrogen sulfide (H 2 S). Luciferase and bisulfite sequencing assays were also utilized to evaluate the CSE promoter activity as well as the methylation status of CSE in transfected cells. Methionine significantly elevated Hcy, TNF‐a, H 2 S, and IL‐1β expression while decreasing the level of CSE in C57BL/6 mice. In contrary, co‐treatment with Methionine and Met reduced the detrimental effect of Methionine. Homocysteine (Hcy) decreased H 2 S expression while promoting the synthesis of IL‐1β and TNF‐α in THP‐1 and raw264.7 cells. Treatment of THP‐1 and raw264.7 cells with methionine and Met reduced the activity of methionine in dose dependently. Moreover, Hcy increased the expression of DNMT and elevated the level of methylation in the CSE promoter, whereas the co‐treatment with methionine and Met attenuated the effects of Hcy. Methionine significantly decreased plasma level of CSE while increasing the severity of inflammatory responses and plasma level of Hcy, which in turn suppressed H 2 S synthesis and enhanced DNA hypermethylation of CSE promoter to promote the pathogenesis of atherosclerosis. In contrary, co‐treatment with methionine and Met reduced the detrimental effect of methionine. Abstract : This study demonstrated that homocysteine treatment reduced the synthesis of H2 S by promoting cystathionine γ‐lyase (CSE) methylation, which might be responsible for the activated inflammation in macrophages and the development of atherosclerosis. Furthermore, metformin (Met) has been shown to promote the production of H 2 S and alter gene expression by modulating DNA methylation. The results of this study demonstrated that Met exerted a beneficial effect on the treatment of atherosclerosis by regulating the production of H 2 S and CSE methylation.